Glaciers : a novel - Smith, Alexis M. (Tin House, 2023)
"Isabel is a single twenty-something in Portland, Oregon, who repairs damaged books in the basement of the local library, dreaming of a life she can't quite reach. She is filled with longing-for a life in Amsterdam even though she's never visited, for the unrequited love of a coworker, for a simpler time from her childhood in Alaska among the threatened glaciers she loves, and for the perfect vintage dress to wear to a party that just might change everything. Unfolding over the course of a single day, Alexis M. Smith's shimmering debut finds Isabel looking into her past-remembering her parents' separation, a meeting with an astrologer, and a life-changing encounter with a glacier-and shows us how fleeting, everyday moments can reveal an entire life. In classic movies, in old photographs and unsent postcards, rare books, and thrifted gems, Glaciers tells the story of a young woman's love of the past and a hope to make something new and all her own"--